User Acceptance of Mobile Library Applications in Academic Libraries: An Application of the Technology Acceptance Model - Yoon, Hye-Young (The Journal of academic librarianship, 2016)
The purpose of this study is to investigate factors influencing user acceptance of mobile library applications in academic libraries. A conceptual structural model for user acceptance of mobile library applications, was developed using a technology acceptance model (TAM) as a theoretical background, and used a structural equation modeling with partial least squares (PLS) approach to examine data collected from a survey of 273 undergraduates in an academic library setting. The results of this study strongly support the TAM theory to understand user acceptance of mobile library applications. Perceived usefulness, interactivity, and ease of use had significant effects on user attitude and intention to use mobile library applications. Further, user satisfaction had the most powerful effect on intention to use among the constructs included in the model. The results are of practical significance to all those interested in the mobile library services field, or primarily academic library researchers and library practitioners. The paper is the first to investigate user acceptance of mobile library services using smartphone applications based on the TAM theory. Simultaneously, the PLS approach used in this study is unique to mobile library services research. The paper, as such, contributes to the methodology development of the mobile library services research field.